Comparing the Efficacy of Compassion-Based Therapy with Cognitive-Behavioral Therapy on Psychological Flexibility and Hope for Life in Cancer Patients - Sharifpour, Ensiyeh; Akbari Amarghan, Hossein; Nejat, Hamid; Iranmanesh, Anis (Health Nexus, 2024)
The diagnosis of this disease, as a highly stressful event and the difficult and complex treatment process, causes significant psychological disturbances in the patient. The purpose of the present study was to compare the effectiveness of compassion-based therapy with cognitive-behavioral therapy on psychological flexibility and hope for life in cancer patients. Research Method: The research method was a quasi-experimental type with pre-test and post-test along with a control group and two experimental groups. The research population included all cancer patients hospitalized in Imam Reza and Omid hospitals in Mashhad in the spring of 2021, among whom 45 individuals were purposively selected and, based on eligibility, entered the study and were allocated to the experimental and control groups with age homogenization. In this study, the Cognitive Flexibility Inventory by Dennis and Vander Wal (2010) and the Snyder Hope Scale (2000) were used. The research hypotheses were analyzed using multivariate analysis of variance and follow-up tests with the multivariate covariance method by SPSS-23 software. Findings: The results showed that both compassion-based therapy and cognitive-behavioral therapy were effective on psychological flexibility (P<0.001) and hope for life (P<0.001) in cancer patients, but there was no significant difference between compassion-based therapy and cognitive-behavioral therapy. Conclusion: It seems that both compassion-based and cognitive-behavioral therapies are effective in reducing psychological problems in cancer patients.